Numerical Simulation and Clinical Implications of Stenosis in Coronary Blood Flow. (1st June 2014) - Zhang, Jun-Mei; Zhong, Liang; Luo, Tong; Huo, Yunlong; Tan, Swee Yaw; Wong, Aaron Sung Lung; Su, Boyang; Wan, Min; Zhao, Xiaodan; Kassab, Ghassan S.; Lee, Heow Pueh; Khoo, Boo Cheong; et al.
Abstract : Fractional flow reserve (FFR) is the gold standard to guide coronary interventions. However it can only be obtained via invasive angiography. The objective of this study is to propose a noninvasive method to determine FF R CT by combining computed tomography angiographic (CTA) images and computational fluid dynamics (CFD) technique. Utilizing the method, this study explored the effects of diameter stenosis (DS), stenosis length, and location on FF R CT . The baseline left anterior descending (LAD) model was reconstructed from CTA of a healthy porcine heart. A series of models were created by adding an idealized stenosis (with DS from 45% to 75%, stenosis length from 4 mm to 16 mm, and at 4 locations separately). Through numerical simulations, it was found that FF R CT decreased (from 0.89 to 0.74), when DS increased (from 45% to 75%). Similarly, FF R CT decreased with the increase of stenosis length and the stenosis located at proximal position had lower FF R CT than that at distal position. These findings are consistent with clinical observations. Applying the same method on two patients' CTA images yielded FF R CT close to the FFR values obtained via invasive angiography. The proposed noninvasive computation of FF R CT is promising for clinical diagnosis of CAD.